2020
DOI: 10.3389/fcimb.2020.00422
|View full text |Cite
|
Sign up to set email alerts
|

Folliculin Controls the Intracellular Survival and Trans-Epithelial Passage of Neisseria gonorrhoeae

Abstract: Neisseria gonorrhoeae, a Gram-negative obligate human pathogenic bacterium, infects human epithelial cells and causes sexually transmitted diseases. Emerging multi-antibiotic resistant gonococci and increasing numbers of infections complicate the treatment of infected patients. Here, we used an shRNA library screen and next-generation sequencing to identify factors involved in epithelial cell infection. Folliculin (FLCN), a 64 kDa protein with a tumor repressor function was identified as a novel host factor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…HEC-1-B and T84 cells on Transwell ® inserts were used as well to study the interaction of gonococci with polarized cells and these studies showed that gonococci weaken the apical junction and polarity of epithelial cells by activating EGFR, which facilitates their transmigration (Edwards et al, 2013). In a more recent study, the role of folliculin in controlling the intracellular survival and trans-epithelial passage of N. gonorrhoeae was shown using renal carcinoma epithelial cells (UOK 257) grown on Transwell ® inserts (Yang et al, 2020). Therefore, such models allow monitoring bacterial interaction with polarized cells, which is not possible when cells are cultivated in 2D.…”
Section: Intestinal and Urogenital Modelsmentioning
confidence: 99%
“…HEC-1-B and T84 cells on Transwell ® inserts were used as well to study the interaction of gonococci with polarized cells and these studies showed that gonococci weaken the apical junction and polarity of epithelial cells by activating EGFR, which facilitates their transmigration (Edwards et al, 2013). In a more recent study, the role of folliculin in controlling the intracellular survival and trans-epithelial passage of N. gonorrhoeae was shown using renal carcinoma epithelial cells (UOK 257) grown on Transwell ® inserts (Yang et al, 2020). Therefore, such models allow monitoring bacterial interaction with polarized cells, which is not possible when cells are cultivated in 2D.…”
Section: Intestinal and Urogenital Modelsmentioning
confidence: 99%
“…Folliculin (FLCN) is a tumor suppressor protein associated with Birt-Hogg-Dube(BHD) syndrome [48,49]. It is involved in many biological processes including vesicular trafficking, energy, and nutrient homeostasis, and monitors E-cadherin protein level [50,51]. Late induction of FLCN in response to P. vivax infection (unpublished) suggests that it might also play an important role in maintaining the integrity of midgut epithelial cells during oocyst bursting or acquisition of nutrients by developing oocyst, though further studies needed to support this hypothesis.…”
Section: Post-invasion Strategy Of P Vivax (Development Of Oocyst)mentioning
confidence: 99%
“…Such interactions lead to GC entry into epithelial cells [17, [24][25][26]. In polarized epithelial cells, GC invading from the apical surface can transcytose through the cell and exit from the basolateral surface [27][28][29]. We have previously shown that GC interaction with polarized epithelial cells induces the disassemble of the apical junction, which allows GC transmigration across the epithelium [14].…”
Section: Introductionmentioning
confidence: 99%